2022
DOI: 10.1111/epi.17450
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of epilepsy with eyelid myoclonia: Delineation of disease subtypes from a large multicenter study

Abstract: Background: Eyelid myoclonia with absences (EMA) has been associated with marked clinical heterogeneity. Early epilepsy onset has been recently linked to lower chances of achieving sustained remission and to a less favorable neuropsychiatric outcome. However, much work is still needed to better define this generalized epilepsy syndrome. Methods:In this multicenter retrospective cohort study, we included 267 EMA patients from 9 countries. The impact of age at epilepsy onset (AEO) on EMA clinical features was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…15 When considering ASM treatment, we documented systematic differences in ASM exposure between females and males, showing a significantly higher use of LEV in the former group and a higher use of VPA in the latter, as observed in other GGE syndromes. 16 In the present study, prognostic factors previously identified in EEM (namely, EM status epilepticus, age at epilepsy onset, and psychiatric comorbidities) 3,4,17 could be confirmed in females only. Conversely, FS, which appeared as a strong predictor of a reduced chance of sustained remission in EEM, 2 were found to be associated with the outcome only in the male sex.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…15 When considering ASM treatment, we documented systematic differences in ASM exposure between females and males, showing a significantly higher use of LEV in the former group and a higher use of VPA in the latter, as observed in other GGE syndromes. 16 In the present study, prognostic factors previously identified in EEM (namely, EM status epilepticus, age at epilepsy onset, and psychiatric comorbidities) 3,4,17 could be confirmed in females only. Conversely, FS, which appeared as a strong predictor of a reduced chance of sustained remission in EEM, 2 were found to be associated with the outcome only in the male sex.…”
Section: Discussionsupporting
confidence: 69%
“…A total of 267 patients (195 females) were included in the present study. 4 Female and male EEM patients did not differ in terms of age at epilepsy onset, follow-up duration, and age at the last follow-up visit (Table 1). Female patients showed a significantly higher rate of ECS (p = .02) and PS persistence (p < .001) at the last visit, combined with a higher rate of a history of migraine (p = .047), whereas male patients showed a higher rate of ID/borderline intellectual functioning (p = .025; Table 1).…”
Section: Demographic and Electroclinical Differences According To Sexmentioning
confidence: 94%
See 3 more Smart Citations